Hegel and the Japanese - An Implication of Hegelian Hegelian logic - Ōhashi , Ryōsuke (Scenari, 2021)
In this essay which echoes in the title the theme of Heideggerian article Hegel and the Greeks, the relationship between Western metaphysical thought as developed in the Hegelian Logic, and Buddhist thought is addressed. To bring the comparison on the level of philosophy, the author refers to the “Japanese”, that is to those Japanese philosophers whose thinking is based on the encounter of Eastern spiritual tradition and Western philosophy. The author compares Hegelian philosophy which could be regarded as a representative of the philosophy of Western reason with the thought of Keiji Nishitani who discusses philosophically the Buddhist prajna. The key-point of the comparison of the author is the identity and the difference of Hegelian “transparency” and Nishitani’s “soku”. The author finds at this “point of intersection” a starting point of further philosophical elucidation of the Buddhist thought in dialogue with Western philosophy.